Analysis Optimization of Switchyard Earthing System Using MATLAB - Deni Almanda; A I Ramadhan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2020)
One of the main factors in securing an electric power system is the earthing system. The earthing system in the generating unit is closely related to the switchyard. Switchyard earthing system analysis is done by adjusting the grid distance and ground rod length to get the most optimal quality and cost combination. The definition of optimal conditions in this case is limited to circumstances where there is a combination of quality that does not exceed the technical tolerance threshold and has cost efficiency. The analysis of the switchyard earthing system was taken as a case study. Calculation results and analysis concluded that the grid distance of 23 m and the length of the 6 m ground rod is the best choice in the optimization of this earthing system by meeting the safety quality criteria for earth resistance is Rg = 0.13806 Ω less than 0.5 Ω with a minimum cost of Rp. 1,220,104,730.Technical standards are carried out based on IEEE Std 80-2000. Calculations for obtaining technical parameters and costs are carried out one-by-one in the range of grid spacing and length of certain ground rods to determine the optimum point using MATLAB-GUI as a programming tool and MATLAB R2011a as a tool mathematical computing.